Intra-Articular Platelet-Rich Plasma, Hyaluronic Acid, and Mesenchymal Stem Cell for Knee Osteoarthritis (2000-2025): A Multi-Database Bibliometric Analysis - Ünlü, Ruhat; Usta, Hasan Emirhan (The European Research Journal, 2026)
Objective: Biologic intra-articular injections, including platelet-rich plasma (PRP), hyaluronic acid (HA), and mesenchymal stem cell (MSC) based therapies, are increasingly investigated for knee osteoarthritis (KOA). However, no comprehensive, multidatabase bibliometric study has compared publication dynamics, thematic evolution, and international collaboration patterns across these modalities. Methods: We searched PubMed, Web of Science, and Scopus for studies published between 2000 and 2025 using standardized terms for KOA and intra-articular PRP/HA/MSC. Records were merged and deduplicated in R (bibliometrix). Descriptive bibliometrics (publication counts, country output) and science mapping techniques (co-authorship networks, thematic co-word analysis) were applied. Figures included annual publication trends, geographic distribution, collaboration networks, thematic networks, and a PRISMA flow diagram. Results: After duplication, 2,291 unique publications were included. PRP-related research grew steeply after 2012 and remained dominant; MSC-related publications expanded rapidly after 2015; HA output was modest and relatively stable. A total of 82 countries contributed, led by the United States (n=2,074) and China (n=1,559), followed by Italy, France, and Spain. Strong bilateral collaborations were observed between Italy and the United Kingdom, the USA–Canada, and Italy–Switzerland. Thematic analysis identified hydrogel, intra-articular HA, and rehabilitation as motor themes, while extracellular vesicles and cartilage regeneration emerged as hotspots. Conclusion: Research on biologic intra-articular injections for KOA has grown substantially, with PRP and MSC driving recent expansion. The field is geographically broad but dominated by North America, China, and Western Europe. Hotspot clusters suggest a shift toward cell-free biologics and regenerative strategies. Our open, reproducible workflow provides a transparent basis for ongoing bibliometric monitoring and evidence synthesis.